2013
DOI: 10.1371/journal.pone.0060704
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Immune Colloidal Gold Strip for Cetacean Meat Restraining Illegal Trade and Consumption: Implications for Conservation and Public Health

Abstract: The consumption of cetacean meat is geographically common and often of undetermined sustainability. Besides, it can expose humans to contaminants and zoonotic pathogens. The illegality of possessing cetacean meat was likely under-reported in some countries due to lack of attention paid by the officials although DNA analysis of market products helped to show such practices. We developed two monoclonal antibodies against synthetic peptides of myoglobin (Mb) for constructing a rapid immune colloidal gold strip. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Some of these have already been utilized to reveal discrepancies in reported marine mammal bycatch, to determine the magnitude of trade and to develop kits that rapidly identify marine mammal species in situ in Asian markets (Baker et al, 2006(Baker et al, , 2007Lukoschek et al, 2009;Lo et al, 2013). These tools, designed specifically for non-specialists, will allow quantitative data collection both on type and volume of marine mammal parts in Asian markets.…”
Section: Lessons and Conclusion From Terrestrial Wildlife Trade Studiesmentioning
confidence: 99%
“…Some of these have already been utilized to reveal discrepancies in reported marine mammal bycatch, to determine the magnitude of trade and to develop kits that rapidly identify marine mammal species in situ in Asian markets (Baker et al, 2006(Baker et al, , 2007Lukoschek et al, 2009;Lo et al, 2013). These tools, designed specifically for non-specialists, will allow quantitative data collection both on type and volume of marine mammal parts in Asian markets.…”
Section: Lessons and Conclusion From Terrestrial Wildlife Trade Studiesmentioning
confidence: 99%
“…Most species are used for human consumption, but some for bait in fisheries (Mintzer et al, 2018). In Taiwan, despite the sale of bycaught cetaceans being illegal, the meat of hundreds of bycaught individuals was once sold in local markets (Sui, 2014), however, recent advances in forensic surveillance have since curtailed most trade (Lo et al, 2013). Information for China is anecdotal and limited, e.g., Jefferson and Van Waerebeek (2002) presented photographic evidence of bycaught common dolphins landed at fish markets of Putian, Fujian Province.…”
Section: Asiamentioning
confidence: 99%
“…Hence, a comparative study was carried out for all eight combinations of antibodies indicated in Table 2. According to the study of Lo et al, the MG content in pork is approximately 2 mg g −1 [31]. Therefore, the ELISA characteristics of the selected pairs of antibodies indicate their suitability for the development of the LFIA with the, practically, demanded sensitivity.…”
Section: Clonementioning
confidence: 99%